Facilites management at football stadium / Mohd Rahfiz Khahirullah - Khahirullah, Mohd Rahfiz (Faculty of Architecture, Planning and Surveying, 2010)
The International Facility Management Association (IFMA) describe that the facility management is a profession that encompasses multiple disciplines to ensure functionality of the built environment. Another broader definition provided by IFMA is: "The practice or coordinating the physical workplace with the people and work of the organization; integrates the principles of business administration, architecture, and the behavioral and engineering sciences." The definition of Facility Management provided by the European Committee for Standardization (CEN) and ratified by BSI British Standards is: “Facilities management is the integration of processes within an organization to maintain and develop the agreed services which support and improve the effectiveness of its primary activities”. The British Institute of Facilities Management has formally adopted the CEN definition but also offers a slightly simpler description: "Facilities management is the integration of multidisciplinary activities within the built environment and the management of their impact upon people and the workplace". In Australia, the term Commercial Services has replaced facilities management in some organizations. Commercial